Gene Editing of the Decoy Receptor LeEIX1 Increases Host Receptivity to Trichoderma Bio-Control - Meirav Leibman-Markus (Frontiers in Fungal Biology, 2021)
Fungal and bacterial pathogens generate devastating diseases and cause significant tomato crop losses worldwide. Due to chemical pesticides harming the environment and human health, alternative disease control strategies, including microorganismal bio-control agents (BCAs), are increasingly sought-after in agriculture. Bio-control microorganisms such as Trichoderma spp. have been shown to activate induced systemic resistance (ISR) in the host. However, examples of highly active bio-control microorganisms in agricultural settings are still lacking, due primarily to inconsistency in bio-control efficacy, often leading to widespread disease prior to the required ISR induction in the host. As part of its plant colonization strategy, Trichoderma spp. can secrete various compounds and molecules, which can effect host priming/ISR. One of these molecules synthesized and secreted from several species of Trichoderma is the family 11 xylanase enzyme known as ethylene inducing xylanase, EIX. EIX acts as an ISR elicitor in specific plant species and varieties. The response to EIX in tobacco and tomato cultivars is controlled by a single dominant locus, termed LeEIX, which contains two receptors, LeEIX1 and LeEIX2, both belonging to a class of leucine-rich repeat cell-surface glycoproteins. Both receptors are able to bind EIX, however, while LeEIX2 mediates plant defense responses, LeEIX1 acts as a decoy receptor and attenuates EIX induced immune signaling of the LeEIX2 receptor. By mutating LeEIX1 using CRISPR/Cas9, here, we report an enhancement of receptivity to T. harzianum mediated ISR and disease bio-control in tomato.